Antibiotic resistance in hospital wastewater in West Africa: a systematic review and meta-analysis - Prince Hotor; Fleischer C. N. Kotey; Eric S. Donkor (BMC Public Health)
Abstract Background The occurrence of antibiotic-resistant bacteria (ARB) has become a global menace and therefore increases morbidity, mortality and healthcare costs. Globally, hospital wastewater (HWW) has been identified as a significant source of antibiotic-resistant elements. Objectives This review aims to systematically review and to perform meta-analyses from evidence on antibiotic resistance studies in HWW in West Africa. Methods The review was conducted in compliance with PRISMA and included studies published between 1990 and 2024 in West Africa from the Scopus, PubMed, and Web of Science databases. Eligible studies that characterized resistant bacteria, genes, or antibiotic residues in HWW were included. Meta-analyses for resistant bacteria and genes as well risk of bias using the Newcastle–Ottawa scale were conducted. Results Out of 23 studies reviewed, resistant bacteria were reported in 39% (E. coli), 26% (K. pneumoniae), and 17% (P. aeruginosa), while 17 studies reported ARGs, with blaTEM (29%), blaOXA- 48 (18%), blaSHV (18%), and mecA (18%) being the most common. Only 4% and 9% of studies focused on toxin genes and antibiotic residues, respectively. Meta-analysis showed pooled prevalence rates for resistant bacteria: E. coli 42.6% (95% CI: 26.7%–60.3%) and K. pneumoniae 32.1% (95% Cl: 28.8%- 36.5%), and ARGs: blaTEM 76.0% (95% CI = 64.6%–84.6%) and blaSHV 59.3% (95% CI = 19.5%–89.8%). Conclusion This systematic review highlights significant findings of high levels of ARGs and ARBs of public health concern in HWW in West Africa. This highlights the need to improve upon the monitoring of antibiotic resistance and treatment of HWW in West Africa.